Ultra-broad range organic solid-state laser from a dye-doped holographic grating quasi-waveguide configuration. (17th July 2017) - Liu, Minghuan; Liu, Yonggang; Peng, Zenghui; Mu, Quanquan; Cao, Zhaoliang; Lu, Xinghai; Ma, Ji; Xuan, Li
Abstract: This paper reports the ultra-broad 149.1 nm lasing emission from 573.2 to 722.3 nm using a simple [4-(dicyanomethylene)-2-methyl-6-(p-dimethylaminostyryl)-4H-pyran] (DCM)-doped holographic polymer-dispersed liquid crystal (HPDLC) grating quasi-waveguide configuration by varying the grating period. The lasing emission beams show s -polarization property. The quasi-waveguide structure, which contained the cover glass, the DCM-doped HPDLC grating, the semiconducting polymer film poly[-methoxy-5-(2′-ethyl-hexyloxy)-1, 4-phenylene-vinylene] (MEH-PPV), and the substrate were confirmed to decrease lasing threshold and broaden lasing wavelength. The operational lifetime of the device is 240 000 pulses, which corresponds to an overall laser duration of more than 6 h at a repetition rate of 10 Hz. In addition, the dual-wavelength lasing range from the 8th and 9th order is over 40 nm. The electrical tunability of the dual-wavelength lasing emission is over 1 nm. The experimental results facilitated the decreased lasing threshold and broadened lasing wavelength range of organic solid-state lasers.